1995
DOI: 10.1254/jjp.67.253
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Clopidogrel, Vapiprost and Argatroban on the Middle Cerebral Artery Thrombosis in the Rat

Abstract: ABSTRACT-This study investigated the roles of thromboxane A2 (TXA2), ADP and thrombin in middle cerebral artery (MCA) thrombosis in the rat. The rat MCA was occluded by a thrombus induced by the photochemical reaction of rose bengal by green light that causes endothelial damage followed by platelet adhesion, aggregation and formation of a platelet and fibrin-rich thrombus at the site of the photochemical reaction. Vapiprost, a specific TXA2-receptor antagonist; clopidogrel, which has the thienopyridine structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 22 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…On the other hand, according to Li et al (1995), in the penumbra around the core, cell death was induced via apoptosis and necrosis. Focal cerebral ischemia was caused in the rat by PIT-MCA occlusion (Umemura et al, 1995). After occlusion, sPLA 2 activity was significantly increased in the cortex, in which the ischemic core and the penumbra coexist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, according to Li et al (1995), in the penumbra around the core, cell death was induced via apoptosis and necrosis. Focal cerebral ischemia was caused in the rat by PIT-MCA occlusion (Umemura et al, 1995). After occlusion, sPLA 2 activity was significantly increased in the cortex, in which the ischemic core and the penumbra coexist.…”
Section: Discussionmentioning
confidence: 99%
“…Occlusion of the photochemically induced thrombotic (PIT) MCA was performed according to the method of Umemura et al (1995). A catheter for administration of rose bengal was placed in the femoral vein.…”
Section: Photochemically Induced Thrombotic Middle Cerebral Artery Ocmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet aggregation studies performed in vitro and in vivo have shown that ADP is an important agonist in platelet-rich thrombus formation [29][30][31][32][33][34][35]. Ticlopidine and clopidogrel specifically inhibit ADP-induced platelet aggregation [9,10,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have found that sPLA 2 -IIA activity in the cerebral cortex was increased after ischemia, and was significantly suppressed by a potent sPLA 2 -specific inhibitor, indoxam (Yagami et al 2002a). Indoxam prevented the neurodegeneration in the penumbra after ischemia, in which apoptosis is caused (Umemura et al 1995). sPLA 2 -IIA caused cell death in primary cultures of rat cortical neurons.…”
mentioning
confidence: 98%